Genotyping ethylene production genes Md-ACS1 and Md-ACO1 for markerassisted selection in apple - Lundmark, Johan (2019)
Texture, firmness and storability are among the most important traits for fruit quality in apple. Consumers are increasingly demanding apples with a “crispy texture”, and the market is offering a premium for a longer shelf life, which has as a result generated an increased interest from plant breeders to meet these demands. The traits are internally regulated by the fruit‟s inherent ethylene production, the suppression of which results in higher firmness retention. Thus far, the ethylene production genes Md-ACS1 and Md-ACO1 represent the best known candidates for enhancing firmness retention during storage. In this study, capillary electrophoresis was used to screen 255 cultivars from Nordic and Baltic germplasm collections for alleles at the Md-ACS1 and Md-ACO1 loci. This was done in order to enable DNA-marker based selections of these genes in breeding material suitable for cool climates. In addition to compiling genotype data, we performed verifications of previously screened cultivars, and additional evaluations of parentage were made in order to determine any pedigree errors. The analysis of the Md-ACO1 locus showed false positives for uncertain reasons, and therefore the true allelic compositions could not be determined. Frequencies of the normal ethylene allele Md-ACS1-1 was much higher in the Estonian (0.94), Finnish (0.95) and Latvian (0.90) collections, whereas the low ethylene allele ACS1-2 was more common in the Lithuanian (0.22), Swedish (0.33) and Norwegian (0.35) collections. Of the previously screened cultivars, 59 showed the expected genotype, with the cultivar „EvaLotta‟ constituting the only exception. In addition, this cultivar was the only genotype that showed any inconsistencies when comparing it to the presumed parents.